2023
DOI: 10.3390/ijms24065997
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Suppresses the Activation of Mast Cells by Modulating the Expression of FcεRI and SHIP1

Abstract: In the present study, we evaluated the effects of kaempferol on bone marrow-derived mast cells (BMMCs). Kaempferol treatment significantly and dose-dependently inhibited IgE-induced degranulation, and cytokine production of BMMCs under the condition that cell viability was maintained. Kaempferol downregulated the surface expression levels of FcεRI on BMMCs, but the mRNA levels of FcεRIα, β, and γ-chains were not changed by kaempferol treatment. Furthermore, the kaempferol-mediated downregulation of surface Fcε… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Kaempferol and other flavonoids including quercetin, luteolin, and nobiletin, are the most vigorously studied polyphenols due to their beneficial effects in the host body, such as anticancer and anti-obesity activities. Previous studies, including ours, reported the anti-allergic effects of flavonoids targeting mast cells (28). Quercetin and luteolin, but not kaempferol, were recently identified as activators of the Aldh1a2 promoter in an assay using the human monocyte cell line THP-1 carrying a reporter plasmid (9).…”
Section: Introductionmentioning
confidence: 54%
“…Kaempferol and other flavonoids including quercetin, luteolin, and nobiletin, are the most vigorously studied polyphenols due to their beneficial effects in the host body, such as anticancer and anti-obesity activities. Previous studies, including ours, reported the anti-allergic effects of flavonoids targeting mast cells (28). Quercetin and luteolin, but not kaempferol, were recently identified as activators of the Aldh1a2 promoter in an assay using the human monocyte cell line THP-1 carrying a reporter plasmid (9).…”
Section: Introductionmentioning
confidence: 54%
“…This anti-inflammatory action may be caused by active compounds in SeNPs and their precursors ( Abdel-Moneim et al, 2022 ). In addition to immunomodulatory and anti-inflammatory properties, it can prevent the production of proinflammatory cytokines ( Attia et al, 2020 , Nagata et al, 2023 ), according to previous studies. Apoptosis may influence the chicks' response to particular intracellular parasite infections and promote the removal of damaged or contaminated cells ( Al-Quraishy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 70%
“…Codium fragile also inhibited inflammatory cytokines such as TNF-α, IL-1β, and IL-6 and nuclear translocation of NF-κB by suppressing the phosphorylation and degradation of IκB-α [ 34 ], and suppressed inflammatory indicators such as COX-2, iNOS, prostaglandin E2, and release of nitric oxide (NO) [ 35 ]. In addition, treatment of kaempferol, as one of the flavonoid compounds, significantly inhibited IgE and lipopolysaccharide-induced inflammation via nuclear factor erythroid 2-related factor 2 (Nrf2)/SHIP1 on bone marrow-derived mast cells (BMMCs) [ 36 ]. In various previous studies, Codium fragile might help significantly inhibit the inflammatory reaction caused by PM 2.5 , and in particular, it is judged to be able to suppress inflammation through the NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%